(untitled) (Research, Society and Development, 2021)
Every day the number of cancer victims increases. In 2020 alone, 626,030 people were affected in Brazil, according to estimates by the National Cancer Institute (INCA). The only way to reduce these numbers is early diagnosis. In the present study, a invention called Ionizographic Detector is described, which performs Positron Emission Tomography (PET) producing metabolic information in breast nodules. This device enables accurate diagnosis of breast nodules regarding its malignancy. To prove its effectiveness, a comparative evaluation was made between the Ionizographic Detector and the Positron Emission Tomography/Computerized Tomography (PET-CT) for analysis of the metabolic data in breast nodules. The research is being carried out with 20 patients who have histopathologically documented breast cancer. From the results it will be possible to prove the device’s efficacy. It will thus enable an accurate and low-cost malignancy diagnosis option. The Ionizographic Detector can be hybridized with some anatomical imaging technology, such as Ultrasound (US). With this, it is possible to promote greater access to accurate diagnoses, significantly increasing the possibility of early diagnoses, enabling a cure or a better prognosis for the patient.